Video analysis of optic-haptic-interaction during hydrophobic acrylic intraocular lens implantation using preloaded injectors - Yan, Weijia; Borkenstein, Andreas; Khoramnia, Ramin; Borkenstein, Eva-Maria; Auffarth, Gerd U. (BMC ophthalmology, 2023)
Objective: To compare the optic-haptic interaction of different hydrophobic acrylic IOLs after using six preloaded injectors.Methods: We reviewed the video-recordings of procedures on a total of 388 eyes that underwent phacoemulsification and intraocular lens (IOL) implantation. For six preloaded injectors: multiSert (Hoya Surgical Optics) [System 1], TECNIS Simplicity (Johnson & Johnson Vision) [System 2], TECNIS iTec (Johnson & Johnson Vision) [System 3], AutonoMe (Alcon, Laboratories) [System 4], Bluesert (Carl Zeiss Meditec) [System 5], and Prosert (OphthalmoPro GmbH) [System 6], we noted in each case the time of IOL delivery and made a descriptive observation of IOL insertion and optic-haptic-interaction.Results: We defined standard haptic behavior where the haptics emerged "folded" from the injector and quickly recovered their pre-implantation appearance. The incidence where the leading haptic emerged in a deformed way for System 1 was 20%, System 2: 19%, System 3: 14%, System 4: 56%, System 5: 24% and System 6: 5%. For trailing haptic deformed behavior, the incidence was 36%, 6%, 4%, 8%, 18% and 2%, respectively for Systems 1 to 6. Optic-haptic adhesion occurred in 2% of cases for System 1, 44% for System 2, 52% for System 3, 48% for System 4, and 11% for System 6 (P < 0.05). Adhesion was not found with System 5.Conclusions: We observed different deformed behavior for leading and trailing haptics in the six preloaded systems, some systems had as much as 52% optic-haptic adhesion.
Gesehen am 07.05.2024